Preliminary study on impact of land use on fish fauna at Kenyana river and its tributaries, Mukah, Sarawak - Hasanaliza, Binti Bujang Abdillah (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The assessment of blackwater fish fauna available at Kenyana River and its tributaries was conducted from 19th March until 21 5t March 2013. The study area is a natural habitat for variety types of blackwater fish including the Asian Arowana. In order to protect this valuable fish and its habitat, the area has been focus to be protected by local authority and it has been marked as sensitive area. Besides that, the area will become one of the ecotourism destinations in Mukah area. The fish sampling were conducted in three days and four sampling stations were chosen which located at Kenyana Lake Information Centre, Kenyana River mouth, Kenyana River and Liwak River) Monofilament gill nets were used (mesh size 5.1 cm, 7.6 cm and 10.1 cm) for fish sampl'fng. Each individual of fish caught were measured for total length, standard length, fork length and body weight. A total of 41 individual of fish were caught with overall 7 blackwater fish species identified which dominated by Pangasiidae (Pangasius macronemus) followed by Cyrprinidae (Anemalichlhys apogon), Notopteridae (Noloplerus chUala), Bagridae (Hemibagrus baramensis), Helostomatidae (Helosloma lemminckii), Osteoglossidae (Scleropages jormosus) and Siluridae (Wallago leerii). Station I (Liwak River) shows the most individual fish caught and the highest species diversity compared to other stations. However, the Shannon-Wiener diversity index H' in Liwak River was low with H' value 0.65 and this illustrate that the fish in Kenyana River and its tributaries were in agitated which might cause by the habitat disturbance in that area. As for species richness '0' in Station 1 was greater with value 1.41 as compared to the other station. Though the diversity index in Station I was high but the opposite result was shown for river water quality. Based on Water Quality Index (WQI), Station I was categorized as Class IV (polluted) and followed by Station 2 (Class III - polluted) and Station 3 (Class III - slightly polluted). The high value of nutrient input at Station 1 and 2 might be due to surface runoff that contained excessive fertilizer drained into the river during raining. Though the fish population was high in Station I with low water quality, this condition might due to the biasness in sampling time frame and method used. Nevertheless, the growing agricultural land use area especially oil palm plantation which located at the middle and upper part of the Kenyana Riv~r and its tributaries might influenced the river condition lead to habitat disturbance.